2023
DOI: 10.1007/s12016-023-08970-4
|View full text |Cite
|
Sign up to set email alerts
|

Vernal Keratoconjunctivitis: A Systematic Review

Gaia Bruschi,
Daniele Giovanni Ghiglioni,
Laura Cozzi
et al.

Abstract: Vernal keratoconjunctivitis (VKC) is a chronic, bilateral corneal and conjunctival problem which typically presents in young individuals. VKC is characterized by itching, photophobia, white mucous discharge, lacrimation, foreign body sensation, and pain due to corneal involvement of shield ulcers. Vernal keratoconjunctivitis is categorized within ocular diseases. The diagnosis is clinical, as no sure biomarkers pathognomonic of the disease have yet been identified. The VKC therapy relies on different types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 195 publications
0
8
1
Order By: Relevance
“…Atopic conjunctival disease is a highly prevalent ocular disorder affecting up to 10.1% of the general population [ 27 , 28 ], with different prevalence according to age. A recent large-scale study reported its prevalence to be 0.3%, 6.6%, 18.3%, 15.8%, 8.1%, and 4.9% in infancy (<1 years), toddlerhood (1–2 years), early childhood (3–5 years), middle childhood (6–11 years), early adolescence (12–18 years), and late adolescence (18–21 years), respectively [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Atopic conjunctival disease is a highly prevalent ocular disorder affecting up to 10.1% of the general population [ 27 , 28 ], with different prevalence according to age. A recent large-scale study reported its prevalence to be 0.3%, 6.6%, 18.3%, 15.8%, 8.1%, and 4.9% in infancy (<1 years), toddlerhood (1–2 years), early childhood (3–5 years), middle childhood (6–11 years), early adolescence (12–18 years), and late adolescence (18–21 years), respectively [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mild disease is typically managed with topical mast cell stabilizers, antihistamines, or dual-acting agents [ 5 , 110 , 111 ]. Mast cell stabilizers work by inhibiting mast cell degranulation, which thereby prohibits the release of pro-inflammatory mediators [ 4 , 6 ]. Mast cell stabilizers have also been shown to act on additional cells involved in ocular allergy, including neutrophils, macrophages, eosinophils, and monocytes [ 112 ].…”
Section: Management Of Vkcmentioning
confidence: 99%
“…Mast cell stabilizers have also been shown to act on additional cells involved in ocular allergy, including neutrophils, macrophages, eosinophils, and monocytes [ 112 ]. Antihistamines block histamine from interacting with their receptors on immune and non-immune cells [ 4 , 6 ]. Most antihistamines target the H1 receptor to provide acute symptomatic relief, whereas mast cell stabilizers exhibit a slow onset of action and aid in chronic management [ 110 ].…”
Section: Management Of Vkcmentioning
confidence: 99%
See 2 more Smart Citations